Sweet Chestnut (Castanea sativa Mill.) Bark Extract: Cardiovascular Activity and Myocyte Protection against Oxidative Damage. (27th February 2013) - Chiarini, Alberto; Micucci, Matteo; Malaguti, Marco; Budriesi, Roberta; Ioan, Pierfranco; Lenzi, Monia; Fimognari, Carmela; Gallina Toschi, Tullia; Comandini, Patrizia; Hrelia, Silvana
Abstract : This work was aimed at evaluating the cardioprotective effects of Castanea sativa Mill. (CSM) bark extract characterized in its phenolic composition by HPLC-DAD-MS analysis. The study was performed using primary cultures of neonatal rat cardiomyocytes to investigate the antioxidant and cytoprotective effects of CSM bark extract and isolated guinea pig left and right atria, left papillary muscle, and aorta to evaluate its direct effect on cholinergic and adrenergic response. In cultured cardiomyocytes the CSM bark extract reduced intracellular reactive oxygen species formation and improved cell viability following oxidative stress in dose-dependent manner. Moreover, the extract decreased the contraction induced by noradrenaline (1  μ M) in guinea pig aortic strips and induced transient negative chronotropic and positive inotropic effects without involvement of cholinergic or adrenergic receptors in the guinea pig atria. Our results indicate that CSM bark extract exhibits antioxidant activity and might induce cardioprotective effect.